Lung Volume Reduction following Recurrent Pneumonia: An Unusual Finding in a COPD Patient - Yihenew Negatu; Philip T. Diaz (Case Reports in Medicine)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease. Frequent pneumonias and exacerbations are known to accelerate its progression. We present a case of severe emphysema whose lung function paradoxically improved following recurrent pneumonia, without lung volume reduction surgery (LVRS). A 54-year-old female with severe COPD presented for LVRS evaluation. She was not a candidate for the surgery because of the unsuitable anatomic distribution of her emphysema. The patient experienced recurrent pneumonia over the years but her lung function and oxygen requirement showed marked improvement. Follow-up imaging studies showed decreased lung volumes and focal fibrotic changes. We believe that the improvement in her lung function overtime is the reflection of lung volume reduction as a result of parenchymal remodeling due to repeated lung infection. These findings seen in our patient contribute important information for the continued effort in developing nonsurgical lung volume reduction techniques.